PENGEMBANGAN MODUL PEMBELAJARAN BERBASIS AUGMENTED REALITY PADA MATERI IPAS SISWA KELAS V SEKOLAH DASAR - Oktipiana, Vika; Jumroh; Noviati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The development of an augmented reality-based learning module on the subject of science for fifth grade elementary school students, has the aim of knowing the development of a valid and practical learning module product. The type of research used in the development of this learning module is R&D (Research and Development), the development uses the ADDIE model consisting of Analysis, Design, Development, Implementation, Evaluation. The subjects of this study were fifth grade students of SD Negeri 14 Muara Telang with a total of 22 students. The data collection techniques used in the study were questionnaires and interviews. The data analysis techniques used were validity analysis and practicality analysis. From the results of the data analysis, it can be concluded that the development of an augmented reality-based learning module on the subject of science for fifth grade elementary school students is categorized as Very Valid and Very Practical.